Pengaruh Pemahaman Peraturan Perpajakan, Sosialisasi Perpajakan dan Edukasi Perpajakan terhadap Tingkat Kepatuhan Wajib Pajak Pegawai Direktorat Navigasi Penerbangan - Sompa, Erika Besse Tenri; Yulianto, Yulianto (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The background to this thesis is non-compliance with employee tax regulations in government agencies. The aim of this research is to influence the understanding of tax regulations, tax socialization and tax education together on the level of taxpayer compliance in employees of the aviation navigation directorate. The research method used was descriptive quantitative through distributing questionnaires, with a population of 180 employees from the aviation navigation directorate and a sample of 45 respondents. Research using validity test analysis, reliability test, multiple regression analysis and coefficient of determination, T test, F test. With the help of SPSS V.27 the research results show that: Understanding tax regulations has a positive and significant effect on employee taxpayer compliance in paying taxes.